2012
DOI: 10.1100/2012/174837
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic, Virucidal, and Antiviral Activity of South American Plant and Algae Extracts

Abstract: Herpes simplex virus type 1 (HSV-1) infection has a prevalence of 70% in the human population. Treatment is based on acyclovir, valacyclovir, and foscarnet, three drugs that share the same mechanism of action and of which resistant strains have been isolated from patients. In this aspect, innovative drug therapies are required. Natural products offer unlimited opportunities for the discovery of antiviral compounds. In this study, 28 extracts corresponding to 24 plant species and 4 alga species were assayed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…Many studies have reported the existence of algae with bioactive compounds that display potent antiviral activity against numerous viruses, such as dengue (Lee et al, 2006;Pujol et al, 2012), avian influenza (Gerber et al, 1958), HIV (Lee et al, 1999;Thuy et al, 2015), human papillomavirus (HPV) (Buck et al, 2006), and picornavirus (Lee et al, 2009). Also, numerous studies have reported algae with antiviral activity against herpes simplex viruses (Faral-Tello et al, 2012;Ribeiro et al, 2012;Hassan et al, 2015). A study performed in Brazil analyzed more than 36 species of algae from its coasts and reported that four of them had significant antiviral activity against both, HSV-1 and HSV-2.…”
Section: Algae-derived Compounds With Antiviral Activity Against Hsvsmentioning
confidence: 99%
“…Many studies have reported the existence of algae with bioactive compounds that display potent antiviral activity against numerous viruses, such as dengue (Lee et al, 2006;Pujol et al, 2012), avian influenza (Gerber et al, 1958), HIV (Lee et al, 1999;Thuy et al, 2015), human papillomavirus (HPV) (Buck et al, 2006), and picornavirus (Lee et al, 2009). Also, numerous studies have reported algae with antiviral activity against herpes simplex viruses (Faral-Tello et al, 2012;Ribeiro et al, 2012;Hassan et al, 2015). A study performed in Brazil analyzed more than 36 species of algae from its coasts and reported that four of them had significant antiviral activity against both, HSV-1 and HSV-2.…”
Section: Algae-derived Compounds With Antiviral Activity Against Hsvsmentioning
confidence: 99%
“…By contrast, Acyclovir demonstrated only minor virucidal effect (IC 50 >200) against HSV-1, as noted by other researchers. 10,26,27 We can assume that the mechanisms of action of thioglucoside 17 are the direct inactivation of virus particles and partially the inhibition of virus attachment and virus binding. It is well known that natural polyphenols are targeted to the HSV-1 glycoproteins, The results are given as mean ± standard deviation (n = 3).…”
Section: Cytotoxicity and Antiviral Activity Of Compoundsmentioning
confidence: 99%
“…Cercopithecus aethiops (green monkey) VERO cells (ATCC CCL-81 (Faral-Tello et al 2012) were cultured in MEM (PAA E15-888) supplemented with 10 percent FBS (PAA A15-151) and 2 mM L-glutamine at 37ºC and 5percent CO2. To perform the experiments, cells were seeded in complete media in 24-well plates on 12 mm-diameter coverslips.…”
Section: Cell Culturementioning
confidence: 99%